Kaitan Hipertensi Dengan Diabetes Mellitus - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
ABSTRACT Ahmad H. Asdie - Association ofIgpertension with diabetes mellitus The clinical impression of association between hypertension and diabetes mellitus has not been consistently confirmed by epidemiological studies. The variety of methodological problems in this area of research includes the choice of appropriate patients and control group, the measurement techniques used, and consideration of many possible confounding variables. Hypertension in diabetes mellitus patients contributes substantially to the increased cardiovascular morbidity and mortality, and should be actively treated as accurately as diabetes mellitus itself. The first therapeuticstep is reduction of overweight, saltintake, and stopsmoking